Identification of Ocular and Auditory Manifestations of Congenital Rubella Syndrome in Mbingo - Imran Jivraj; Chris J. Rudnisky; Emmanuel Tambe; Graham Tipple; Matthew T. S. Tennant (International Journal of Telemedicine and Applications)
Purpose. Congenital rubella syndrome (CRS) is a global cause of preventable hearing impairment, blindness, and intellectual impairment. The present study sought to identify ocular and auditory manifestations of CRS in school-aged children in Mbingo, Cameroon. Design. Cross sectional study. Subjects. Students at two schools, one for children with hearing impairment, were screened for cataract, congenital glaucoma, and pigmentary retinopathy. Methods. Students underwent seven-field digital fundus photography through a dilated pupil using a Topcon NW200 nonmydriatic camera. Images were assessed by retina specialists in Canada via teleophthalmology. Clinical evidence was integrated to form case definitions for CRS based on Center for Disease Control and Prevention guidelines. Serological evidence of rubella infection was obtained using standardized IgG antibody titers. Main Outcome Measure. Number of probable and suspicious cases of CRS. Results. Between September 2009 and May 2010, 320 students participated. There were 28 (10.2%) probable cases, 104 (37.8%) suspects, and 143 (52.0%) unaffected. Rubella IgG serology was positive in 79 (48.7%) of children with hearing impairment and 11 (7.4%) of children with normal hearing. Conclusions. The present study identified 28 probable cases of CRS. Furthermore, 92.6% of students with normal hearing did not possess rubella IgG antibodies making future cases of CRS likely without intervention.